Milet, Türkei. Marmor in Milet der Kaiserzeit. Bericht über die archäometrische Studie. Die Arbeiten der Jahre 2018 bis 2022 - Toma, Natalia (e-Forschungsberichte des DAI, 2023)
The report presents the archaeometrical methods used to provenance the marble building material used to adorn the city of Miletus. Within the framework of the DFG-funded research project (TO1102/1-1), more than 440 archaeological and geological samples were examined during the period 2018 to 2022, and each was provided with an archaeometric dataset containing numerical parameters and descriptively recorded properties, which serves as the basis for a multivariate provenance analysis of the marble. In addition, two collections of geological material and archaeological samples were recorded: the legacy of Klaus Germann (TU-Berlin), which is now preserved at the Antikensammlung in Berlin, and the collection of Gregor Borg stored at the Martin-Luther-University of Halle.